EXPLORING THE MINDSET TO BECOME AN ENTREPRENEUR - Bernardus, Denny; Aji, Imanuel Deny Krisna; Padmawidjaja, Liestya; Murwani, Fulgentius Danardana; Hitipeuw, Imanuel; Jatiperwira, Stefan Yudana (Universitas Brawijaya, Indonesia, 2023)
Universitas Ciputra Surabaya is one of the universities that strongly supports its students to become excellent entrepreneurs by providing entrepreneurship curriculum and real business practice experiences. An entrepreneurial mindset is required to achieve this goal. This research aims to elaborate on the dimensions of entrepreneurial mindset based on previous research findings. Adopting a mixed-method approach on undergraduate students who have taken entrepreneurship courses. Data analysis was conducted through semi-structured interviews and confirmatory factor analysis to test the dimensions of entrepreneurial thinking generated from qualitative research. These were then tested on 100 students enrolled in entrepreneurship courses. The research results indicate two dimensions of entrepreneurial mindset: elaborating mindset with indicators of consideration, planning, and information seeking, and implementing mindset with indicators of action and evaluation. The confirmatory factor analysis results show that the elaborating mindset is focused on planning, such as planning/strategies for starting a business and when to start a business, while the implementing mindset is focused on evaluation, such as always seeing opportunities and measuring these opportunities in starting one's own business. For universities that provide entrepreneurship education, students need to be given materials on creating business plans and evaluating the businesses they are running.